The Value of Social Care Character Education Through Merindu Baginda Nabi - Alfa Rosyid Abdullah; Herman J. Waluyo; Nugraheni Eko Wardani (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
Character education is a form of cultivation of noble character in students. The aspect of 'social care' character is one of the most important of the eighteen character education in Indonesia, this is because the sense of sensitivity and help towards others in the environment around students begins to diminish. There are various kinds of media to succeed in internalizing character education, one of which is a novel. The novel Merindu Baginda Nabi by Habiburrahman El-Shirazy can be said to be a complete novel in instilling character in Indonesia. Therefore, researchers will explore how the value of social care character education in the novel Merindu Baginda Nabi. The research method used is qualitative descriptive qualitative research. The novel Merindu Baginda Nabi as a source of data in this study, in the form of dialogue and narrative stories about character education about social care. Based on the results of the analysis, seventeen data were found that were divided into four important parts, namely: giving help to others, caring for others, mutual respect, and sympathy.